Investigation of dry cutting performance in lathes machine using flat heat pipes as part of cooling system - Ragil Sukarno; Fajrin Rizqi Nurrakhmat; Syamsuir Syamsuir; Mukhsinun Hadi Kusuma (Jurnal POLIMESIN, 2023)
This study aims to develop a cutting tool cooling system for lathe machines in dry machining using finned flat heat pipes. The heat pipe is equipped with fins placed at the cutting tool's edge to reduce the cutting tool's temperature. Tests were conducted on conventional lathes with spindle speeds varied from 250 rpm, 540 rpm, and 850 rpm for the 20-minute operation to reduce the workpiece diameter from 22 to 18 mm and 90 mm long. The testing was carried out in three methods: (1) dry cutting process without heat pipe and coolant, (2) cutting process without heat pipe but using coolant, (3) dry cutting process equipped with heat pipe without coolant fluid. The result shows that using heat pipes as a cooling medium significantly influences reducing the cutting tool temperature compared with the dry machining process. The cutting tool temperature can be maintained at 30–40oC when using a heat pipe as part of the cooling system. Using heat pipes as a cutting tool cooling medium also positively affects the cutting tool's life. During the 20-minute with spindle speed 250 rpm machining process, the cutting tool assisted with the heat pipe has not shown wear, while the cutting tool in the dry machining process began to show wear. On the other hand, the cooling process using coolant liquid gives maximum results, so a combination of heat pipes and coolant fluid with a minimum capacity can be recommended as part of the cooling system to improve the cutting tool's performance.